Production, marketing and value chain mapping of 'Srijana' tomato hybrid seed in Nepal - Magar, D.B.T.; Gauchan, D. (Nepal Agricultural Research Council, 2016)
A tomato variety known as ‘Srijana’ developed by Nepal Agricultural Research Council (NARC) has been substantially popular among Nepalese farmers and entrepreneurs. To understand the seed value chain of the Srijana hybrid tomato, a survey was conducted in 2014/15 with public research and extension institutions, private seed companies/firms, non-governmental organization and community group including individual farmers, involved in Srijana tomato seed production. The survey covered random selection of 30 agro-vets and 30 farmers in Kathmandu valley, Kavre, Nuwakot, Dolakha and Kaski districts, where production of Srijana tomato seed is mostly concentrated. A focus group discussion was also conducted with commercial tomato farmers in each of the study districts. The study showed a total production of 293 kg Srijana seed having a value of around 47 million Nepalese Rupees (NRs equivalent to US $ 470 thousands) in year 2013/14. Private sector was the dominant actor sharing about 85% of the total Srijana seed production followed by non-governmental organization (10%), farmers group (3%) and governmental station/farm/centers (2%), respectively. Out of the total Srijana seed produced, about 95% was consumed in domestic market, while 5% was exported to India. The study revealed increasing trend of production, supply and price of Srijana tomato seed. Approximately 0.3 million NRs (US $ 3,000) profit was estimated through the production of Srijana tomato seed in 0.05 hectares (500 m2) of land area. Agro-vets (private sector seed dealers) were the major actors receiving higher profit margins for supplying the seed from producers to farms. The farmers producing and selling the seed with technical assistance of public agencies received higher producer`s share (66.6%) than farmers producing and selling seed through own group (60%), technical assistance of non-governmental organization (53.3%), and in contract with private seed companies (26.7%). Majority of commercial tomato farmers had complaints on supply of poor quality seed in the market. As a result, there was declining faith on the quality of Srijana tomato seed. Limited access to parental lines and poor availability of skilled human resources were the key constraints to produce the quality Srijana seed. Therefore, it is recommended that there should be a provision of efficient quality control mechanisms, and development of human resources including public private partnerships for maintaining the genetic purity of parental lines and also improving the capacities of seed value chain actors for sustainable Srijana seed production in Nepal.